(untitled) (Dhaka University Law Journal, 2025)
Growing concerns over the environmental impact of global trade have led to increasing scholarly and policy attention to how international trade intersects environmental regimes. There emerges a substantial consensus among researchers and policymakers that multilateral trade agreements (MTAs) frequently intersect- and often conflict- with multilateral environmental agreements (MEAs), resulting in adverse consequences for the environment. In this context, this article explores the role and challenges of the World Trade Organization (WTO) in reconciling global trade and environmental governance. It critically examines how the WTO’s institutional structures and procedural mechanisms have an impact on environmental outcomes across countries. The article concludes by outlining potential pathways for the WTO to enhance its relevance and effectiveness in addressing both trade and the environment. Dhaka University Law Journal, 2025, 36 (1), 85-100